Methodology of the physicians education on the studying cycles of the Department of Combustiology and Plastic Surgery in modern environment - G. P. Kozynets; O. A. Zhernov; V. P. Tsygankov; V. G. Shendryk (Клінічна хірургія)
Methodology of the physicians education on the studying cycles of the Department of Combustiology and Plastic Surgery in modern environment